Nanomechanical behavior of polystyrene/graphene oxide nanocomposites - Mohammadsalih, Zaid G.; Mullin, Nicholas; Amarie, Sergiu; Danilov, Artem; Ur Rehman, Ihtesham (Taylor and Francis Ltd., 2024)
The in-situ investigation of the nanomechanical features of the polymer graphene nanocomposites has become a challenging and an indispensable task to achieve the required application. Graphene oxide (GO) nanocomposites were prepared at 1.0 weight fraction of GO to reinforce polystyrene (PS) using solution blending approach. The morphology of the resulting nanocomposites was characterized by optical, scanning electron, transmission electron, atomic force, and scattering scanning near-field optical microscopies. These showed a uniform dispersion of graphene oxide nano-sheets in the PS matrix. By adopting Derjaguin–Muller–Toporov (DMT) formula, the nanomechanical properties for the cryogenically fractured surface of the composites were characterized using the traditional atomic force microscopy (AFM), peak-force quantitative nanomechanical mapping (QNM), and tip-force mode functioned with scattering scanning near–field optical microscopy (s-SNOM). Young’s modulus of the PS matrix varied around (1–2) GPa as shown by QNM and s-SNOM similar to what was reported in the literature. However, while putative GO nano-sheets were measured to have a higher elastic modulus than the surrounding matrix in Peak-Force QNM experiments, they were significantly below literature values. By using Tip-Force mode related to s-SNOM, the expected values of Young’s modulus for GO were recovered.